2007
DOI: 10.1158/1078-0432.ccr-06-2027
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-Specific Methylation in Saliva: A Promising Biomarker for Early Detection of Head and Neck Cancer Recurrence

Abstract: Purpose: Our goal was to define tumor and saliva gene methylation profile of head and neck squamous cell carcinoma and to evaluate its prognostic significance and its biomarker potential for early detection of relapse. Experimental Design: We prospectively analyzed 11 genes by methylation-specific PCR on primary tumors, histologically normal adjacent mucosa, and saliva from 90 French patients at diagnosis and during follow-up as well as on 30 saliva specimens from control-matched patients with nonmalignant hea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
131
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 171 publications
(143 citation statements)
references
References 34 publications
8
131
0
4
Order By: Relevance
“…In our cohort of patients with laryngeal and hypopharyngeal cancer, we did not observe any correlation between mortality and hypermethylation of any of the 4 investigated genes, either alone or in combination. Similarly, some previous investigators did not observe any effect of either p16 hypermethylation or MGMT hypermethylation on the prognosis for patients with head and neck cancer 29,30 and esophageal cancer 11 ; whereas the results from other studies 5,8 suggested a role of MGMT hypermethylation in the survival of patients with head and neck cancer. An association between aberrant gene methylation and the development of SPTs has been suggested.…”
Section: Discussionmentioning
confidence: 57%
“…In our cohort of patients with laryngeal and hypopharyngeal cancer, we did not observe any correlation between mortality and hypermethylation of any of the 4 investigated genes, either alone or in combination. Similarly, some previous investigators did not observe any effect of either p16 hypermethylation or MGMT hypermethylation on the prognosis for patients with head and neck cancer 29,30 and esophageal cancer 11 ; whereas the results from other studies 5,8 suggested a role of MGMT hypermethylation in the survival of patients with head and neck cancer. An association between aberrant gene methylation and the development of SPTs has been suggested.…”
Section: Discussionmentioning
confidence: 57%
“…Detection of aberrant methylation of ECAD, MGMT, DAPK, RARb, FHIT, p16, p15, TIMP3, and APC in saliva samples from patients with oral cancer 14 and of HIN-1 and WIF-1 in oral cancer tissue samples has been reported previously. 22,23 Although the aberrant methylation of TMEFF2 and SPARC has been reported …”
Section: Candidate Genes For Oral Cancer Detectionmentioning
confidence: 52%
“…[10][11][12][13] Therefore, the determination of DNA methylation status may represent a target for identifying OSCC, and the creation of methylation gene panels could be useful for OSCC screening to assist in its early detection, monitoring, and treatment. 12,13 Several studies to date have attempted to detect OSCC using aberrant DNA methylation in samples obtained from oral rinses or saliva 14,15 ; however, the reported sensitivities and specificities of the methods for cancer detection have not been sufficient to justify their use as screening tests for OSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Serial analysis of serum or biofluid DNA methylation patterns may one day enable the detection of early relapse before it manifests with clinical symptoms or on routine imaging, affording an extended window in which cure may still be achievable. One small prospective study has already shown that gene methylation (panel of 10 genes) in saliva is a promising biomarker for the follow-up and early detection of still curable relapses of head and neck squamous cell carcinoma patients (Righini et al, 2007).…”
Section: Epigenomic Profiles As Markers Of Tumour Prognosismentioning
confidence: 99%